The law of refugee status - Hathaway, James C.; Foster, Michelle, 1972- (Cambridge University Press, 2014)
"The first edition of The Law of Refugee Status (published in 1991) is generally regarded as the seminal text on interpreting the refugee definition set by the UN's 1951 Refugee Convention. Its groundbreaking analysis served as the bedrock for not only much judicial reasoning, but also for a burgeoning academic literature in law and related fields. This second edition builds on the strong critical focus and human rights orientation of the first edition, but undertakes an entirely original analysis of the jurisprudence of leading common law and select civil law states. The authors provide robust responses to the most difficult questions of refugee status in a clear and direct way. The result is a comprehensive and truly global analysis of the central question in asylum law: who is a refugee?"--